Food Insecurity and Family Well-Being Outcomes among Households with Young Children - Johnson, Anna D.; Markowitz, Anna J. (The Journal of pediatrics, 2018)
To investigate associations between household food insecurity and multiple family well-being variables in an effort to illuminate previously understudied, policy-amenable mechanisms through which food insecurity threatens healthy development. Data are drawn from the nationally representative Early Childhood Longitudinal Study—Birth Cohort. The Early Childhood Longitudinal Study—Birth Cohort contains longitudinal data on household food insecurity and several family well-being factors including maternal physical and mental health, positive parenting practices and disciplinary strategies, and frequency and severity of spousal conflict. We use regression models with lagged dependent variables to estimate associations between food insecurity and family well-being outcomes, on a subsample of low-income families (N ≈ 2100-4700). Household food insecurity was significantly associated with poorer maternal physical health; increased depressive symptoms and use of harsh discipline strategies; and greater frequency and negativity of conflict between parents. Associations were strongest and most consistent when children were preschool aged. Transitions into food insecurity between toddlerhood and preschool were also associated with significantly worse parental physical and mental health outcomes, and more family conflict, with similar though slightly weaker and less consistent associations for transitioning into food insecurity between infancy and toddlerhood. Food insecurity is associated with significant decreases in family health and well-being. Clinicians and other public health officials play a critical role in assessing risk for children and families, and linking families with supportive services. Screening families experiencing or at risk for food insecurity and connecting them with resources is an avenue through which public health practitioners can support family health.